2022
DOI: 10.1037/per0000517
|View full text |Cite
|
Sign up to set email alerts
|

Borderline personality disorder in adolescence: The role of narrative identity in the intrapsychic reasoning system.

Abstract: Borderline personality disorder (BPD) manifests in adolescents, serving as a forerunner for later dysfunctionality and life constraints. BPD is characterized by multiple difficulties in understanding the self and others, and it has been implied that intrapsychic processes of reasoning might be the primary driver of these disturbances. In this study, we examined the role of narrative identity, the dynamic and evolving story people construct about their personal pasts, presents, and futures, as a potentially imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 61 publications
1
6
0
Order By: Relevance
“…With regard to motivational themes , it appeared that—in line with previous findings—youth with an avoidant personality trait facet profile narrated less communal and less agentic stories, youth with a schizotypal personality trait facet profile less communal stories and youth with a borderline profile less agentic stories (Cowan et al, 2021; Holm et al, 2018; See et al, 2021). Lower levels of both agency and communion have frequently been studied and mainly reported in patients with BPD (e.g., Lind, Vanwoerden, et al, 2022; Sajjadi et al, 2022). This study’s mixed findings point to the importance of considering motivational themes across the complete spectrum of personality pathology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to motivational themes , it appeared that—in line with previous findings—youth with an avoidant personality trait facet profile narrated less communal and less agentic stories, youth with a schizotypal personality trait facet profile less communal stories and youth with a borderline profile less agentic stories (Cowan et al, 2021; Holm et al, 2018; See et al, 2021). Lower levels of both agency and communion have frequently been studied and mainly reported in patients with BPD (e.g., Lind, Vanwoerden, et al, 2022; Sajjadi et al, 2022). This study’s mixed findings point to the importance of considering motivational themes across the complete spectrum of personality pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Communion represents the need for connection through love and intimacy (“to get along”; McAdams & Pals, 2006). Thwarted agency and communion themes have been associated with BPD characteristics in inpatient adolescents (of whom it is unclear whether or not they were formally diagnosed with a PD; Lind, Vanwoerden, et al, 2022). Furthermore, low levels of agency and communion were associated with BPD characteristics in university students and adult patients diagnosed with BPD (e.g., Adler et al, 2012; Lind, Vanwoerden, et al, 2022).…”
Section: Narrative Identity Development and Personality Pathology: Wh...mentioning
confidence: 99%
“…The individual's developmental stage [Chrono-Level; ( 10 )] should also be considered in terms of when and what Micro-Level stories are most influential to the individual. For example, adolescence constitutes a particularly sensitive period for developing PD ( 20 ) and it is also within this period a disturbed narrative identity begins taking shape ( 21 , 22 ). Thus, focusing on the maladaptive narrative ecology seems highly relevant in adolescents at risk of developing PD.…”
Section: The Micro-meso Level In Pdmentioning
confidence: 99%
“…Traits continue to play an important part in defining personality, but values, motivations, and identity begin to interact with traits and the environment to provide a fuller account of personality function. Identity function, I have argued, most closely aligns with LPF in its overlap with self-function and reliance on metacognitive function (mentalizing capacity), such that it explains the onset of personality disorder in adolescence if not scaffolded properly as young people begin to consolidate their identity (Sharp, 2020; Sharp & Wall, 2018, 2021; Sharp & Cano, 2018; Sharp et al, 2018). Although this conclusion can only be verified with longitudinal data specifically designed to test this hypothesis, we do, for instance, know that personality disorder first onsets in adolescence and not before, despite the fact that some preadolescents may display extreme traits (Stepp et al, 2010).…”
mentioning
confidence: 95%
“…Although this conclusion can only be verified with longitudinal data specifically designed to test this hypothesis, we do, for instance, know that personality disorder first onsets in adolescence and not before, despite the fact that some preadolescents may display extreme traits (Stepp et al, 2010). We also know that young people with personality pathology struggle with mentalizing (Sharp et al, 2011) and coherence in narrative identity (Lind et al, 2019, 2020, 2021). Recently, we have also demonstrated that maladaptive traits measured in preadolescence are associated with maladaptive daily identity function in early adulthood via problems in interpersonal function during early adolescence (Vanwoerden et al, 2021).…”
mentioning
confidence: 99%